2010
DOI: 10.3727/096368910x508924
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Liver Tissues under the Kidney Capsule Site Provides Therapeutic Effects to Hemophilia B Mice

Abstract: Recent advances in liver tissue engineering have encouraged further investigation into the evaluation of therapeutic benefits based on animal disease models. In the present study, liver tissues were engineered in coagulation factor IX knockout (FIX-KO) mice, a mouse model of hemophilia B, to determine if the tissue engineering approach would provide therapeutic benefits. Primary hepatocytes were isolated from the liver of wild-type mice and suspended in a mixture of culture medium and extracellular matrix comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Although liver organ transplantation has cured patients with hemophilia A and B (Gordon et al, 1998), shortages of available livers have greatly limited the ability of liver transplantation to become a standard treatment. In earlier proof-of-concept studies, our laboratory has demonstrated the therapeutic value of cell-based approaches for hemophilia, including hepatocyte transplantation and liver tissue engineering (Tatsumi et al, 2008b;Ohashi et al, 2010). These successful experiments prompted us to generate FIXproducing cells from an autologous tissue origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although liver organ transplantation has cured patients with hemophilia A and B (Gordon et al, 1998), shortages of available livers have greatly limited the ability of liver transplantation to become a standard treatment. In earlier proof-of-concept studies, our laboratory has demonstrated the therapeutic value of cell-based approaches for hemophilia, including hepatocyte transplantation and liver tissue engineering (Tatsumi et al, 2008b;Ohashi et al, 2010). These successful experiments prompted us to generate FIXproducing cells from an autologous tissue origin.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based therapies have received a great deal of attention as a next-generation therapeutic approach for hemophilia (Oh et al, 2006;Follenzi et al, 2008;Kasuda et al, 2008;Tatsumi et al, 2008a,b;Ohashi et al, 2010). There has been enormous interest in the transplantation of stem cells to produce clotting factors (Chuah et al, 2004;Oh et al, 2006;Coutu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based therapy has attracted great attention as a curative therapeutic option for haemophilia [11][12][13]28,29]. Because coagulation factors are mainly produced in the liver, the liver is a reasonable target site for cell transplantation [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as a preclinical study, our group investigated the therapeutic effect of hepatocyte-based therapy on hemophilia mice. Specifically, primary hepatocytes isolated from the liver of wild-type mice were intraportally transplanted to the liver of hemophilia B mice [ 76 ], or transplanted under the kidney capsule of hemophilia B mice as a mixture with EHS gel [ 77 , 78 ]. In both experiments, 1 to 3% increase of plasma FIX activity levels was observed in the recipient mice after the procedures, and persisted for a long-term period without development of FIX-neutralizing antibody.…”
Section: Cell Sheet Technology As a Novel Therapeutic For Hemophiliamentioning
confidence: 99%